2005
DOI: 10.1152/jn.00230.2004
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity During Predictable and Unpredictable Weight Changes When Lifting Objects

Abstract: When humans repetitively lift the same object, the fingertip forces are targeted to the weight of the object. The anticipatory programming of the forces depends on sensorimotor memory representations that provide information on the object weight. In the present study, we investigate the neural substrates of these sensorimotor memory systems by recording the neural activity during predictable or unpredictable changes in the weight of an object in a lifting task. An unpredictable change in weight leads to errone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 59 publications
5
58
0
Order By: Relevance
“…This is consistent with our previous fMRI experiment, in which we found right-sided supramarginal activation when the weight of the object was changed in an irregular manner compared with when the same weight was lifted in consecutive lifts (Schmitz et al, 2005). Because a block design was used in the previous study, the present results obtained by an event-related design provide more compelling evidence that the supramarginal cortex is activated at the time point when the weight is actually changed.…”
Section: Mismatch Between Predicted and Actual Weight And Updating Ofsupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with our previous fMRI experiment, in which we found right-sided supramarginal activation when the weight of the object was changed in an irregular manner compared with when the same weight was lifted in consecutive lifts (Schmitz et al, 2005). Because a block design was used in the previous study, the present results obtained by an event-related design provide more compelling evidence that the supramarginal cortex is activated at the time point when the weight is actually changed.…”
Section: Mismatch Between Predicted and Actual Weight And Updating Ofsupporting
confidence: 92%
“…In our previous study (Schmitz et al, 2005), we also found activity in the right inferior frontal cortex (area 44) in lifting series with predictable or unpredictable weight changes. This finding could not be confirmed in the present study.…”
Section: )supporting
confidence: 55%
See 3 more Smart Citations